Acceleration of the Battery Electric Vehicle Program through Carbon Tax and Strategic Management between Government Institutions - Sarjana, Sri; Claudia, Sindy Allaam; Ramadhina, Assyifa Tasma; Suyanti, Lilis (RSF Conference Series: Engineering and Technology, 2023)
The implementation of the Sustainable Transport Strategy aims to reduce global warming through the generation of environmentally friendly energy, the reduction of carbon emissions and the fight against extreme climate change. The use of vehicles in Indonesia, most of which still use gasoline-fueled motor vehicles, produces polluting emissions and can cause various problems. This study aims to find solutions to government policy management to realize the transition to sustainable transportation through battery electric vehicles. This study uses a descriptive qualitative research design. Data collection in this study using literature studies by collecting sources on the concept of sustainable development in the field of transportation, in the context of renewable energy. The data processing process carried out in qualitative descriptive research includes data reduction, data presentation, and verification or inferring data. The analysis technique used is in-depth analysis which means in-depth analysis techniques. The results show that, to answer these problems, the Indonesian government needs to increase the use of electric motor vehicles both for public and private vehicles and the right policy-making strategy is needed to target the acceleration of battery electric vehicle program can be significant. Through carbon tax policies and supporting consumer convenience which includes the construction of charging station infrastructure, spare parts distribution, and increasing mechanical competence, the level of public awareness to switch to using battery electric vehicles.